AN ANALYSIS OF ERRORS ON THE USING SIMPLE PAST IN WRITING A NARRATIVE TEXT - Umar Umar (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2015)
This study aimed to examine errors on past tense in a writing a narrative text of by 12 participants. The participantswere second semester students of English Education Department of STKIP Paracendekia NW Sumbawa in theacademic year 2014/2015. This research was a descriptive qualitative research. The instrument used for this studywas participants’ written narrative texts. The results of the study show that there were errors committed by theparticipants on using past tense. All of the errors on using past tense in the written narrative texts was identified andclassified; these were addition, omission, and misformation.These aspects of writing in English pose the most difficultproblems to participants. This study has shed light on the manner in which students internalize the rules of the targetlanguage, which is English. Such an insight into language learning problems is useful to lecturers because it providesinformation on common trouble-spots in language learning which can be used in the preparation of effective teachingmaterials.